Tingkat Kesehatan Bank dan Kualitas Laba: Perbandingan Sebelum dan Sesudah Implementasi PSAK 71 - Ramadani, Ramadani (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2026)
Research aims: This study aims to examine the effect of bank health indicators—including Non-Performing Loans (NPL), Good Corporate Governance (GCG), Return on Assets (ROA), and Capital Adequacy Ratio (CAR)—on earnings quality of Regional Development Banks (BPD) in Indonesia, and to test the moderating role of Allowance for Impairment Losses (CKPN) before and after the implementation of PSAK 71. Design/Methodology/Approach: The research uses a quantitative approach with panel data regression analysis on 24 BPDs in Indonesia over the period of 2016–2023. Hypothesis testing was preceded by classical assumption tests to ensure model validity. Research findings: The study finds that bank health indicators simultaneously affect earnings quality both before and after PSAK 71. Individually, GCG, ROA, and CAR significantly affect earnings quality, while NPL does not. However, CKPN significantly moderates the overall relationship between bank health and earnings quality only after PSAK 71 implementation, suggesting that expected credit loss-based provisioning increases the relevance of credit risk management in influencing earnings quality. Theoretical contribution/Originality: This research extends the literature on earnings quality by incorporating PSAK 71's impact and positioning CKPN as a moderating variable. It provides empirical support for the role of accounting standard changes in reshaping the relevance of financial indicators in assessing earnings quality. Practitioner/Policy implication: The results offer insights for regulators and bank managers to enhance transparency and financial reporting quality post-PSAK 71. The findings underscore the need for strengthened provisioning strategies and risk oversight to support sustainable earnings quality in regional banks.